TRINITY OF SEVERE ACUTE RESPIRATORY SYNDROME CORONAVIRUS-2: ORIGIN, GENOTYPE, PHENOTYPE, AND IMMUNE RESPONSE IN CORONAVIRUS DISEASE-2019 - NANDAGOPAL, MURUGAN; BALAKRISHNAN, ARULMOZHI; PADHIAR, CHIRAYU (Asian Journal of Pharmaceutical and Clinical Research, 2021)
The coronavirus disease-2019 (COVID-19) outbreak by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) or a novel coronavirus (2019-CoV) has prompted global health concerns. A pandemic resulted from the disease’s transmission through many routes. In this pandemic, the interaction between coronavirus and the host immune system, particularly the innate immune system, is becoming more prominent. Against viruses and pathogens, innate immunity serves as a first line of defense. Our understanding of pathogenesis will benefit from a better grasp of the mechanisms of immune evasion techniques. The origin, classification, structure, and method of transmission of SARS-CoV-2 were summarized in this paper. We have discussed the importance of important communications. In this review, we have discussed the function of important components of the innate immune system in COVID-19 infection, as well as how the virus evades innate immunity through multiple tactics and contributes to a wide range of clinical symptoms and outcomes.